A Practice of Social Medicine - Sidney Kark; Emily Kark (Social Medicine Publication Group, 2006)
Social medicine may be regarded as a practice of medicine concerned with health and disease as a function of group living. It is interested in the health of people in relation to their behaviour in social groups and as such is concerned with care of the individual patient as a member of a family and of other significant groups in his daily life. It is also concerned with the health of these groups as such and with that of the whole community as a community. Concern with the health needs of larger communities and territorial groups such as cities, regions and nations is also an important area of social medicine in which the public health physician is involved. Special interest groups have been the focus of attention of yet other practitioners of social medicine. Children at school, university students and occupational groups are among the more important of these groups for whom special health services, oriented to their specific needs, have been developed. Less formal groupings are now receiving increasing attention by those concerned with community health services, such as the family, in which the relationships between the members have intimate and enduring qualities. Other significant informal groups, in which face-to-face relationships are characteristic, are friendship groups, play groups of children and the neighbourhood community, in rural village or urban neighbourhood.